PENGARUH PUPUK KANDANG DAN INOKULASI MIKORIZA VESIKULAR ARBUSKULAR TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L) - Bakti Utama; E. Tadjudin S.; Amran Jaenudin (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2019)
Fertilizer has a function as being able to improve soil properties and chemistry, as well as soil biology. From the decomposition process, soil fertilizer will produce a topsoil fraction that can be made with soil particles made by soil humus complexes, so that it becomes more stable which will further reduce the rate of air infiltration in the soil. The granting of arbuscular vesicular mycorrhizae inoculation is one of the collaborative works of fungi, soil and plant roots which supports the supply of nutrients for plants, improves soil structure, and provides resources to promote unfavorable plant growth. The purpose of this study was to study the best interaction between the dose of fertilizer and mycorrhizal VA on the growth and yield of shallots. The design used was an experimental method with randomized block design (RBD). This study consisted of two factors, namely the dose of chicken fertilizer and the arbuscular vesicular mycorrhiza inoculation. The 15 ton / ha fertilizer application showed the best increase in red 3.90 kg / plot or equal to 17.33 tons / ha and the arbuscular vesicular mycorrhizae 4 tons / ha showed the best results on the growth and yield of shallots on dry weight tubers per plot which produces 3.60 kg / plot or the equivalent of an average yield of 16 tons / ha.